The role of social media marketing and brand experience in increasing brand loyalty through customer engagement for mpv car users in Medan - Indawati Lestari; Desy Astrid Anindya; Finta Aramita (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In the rapidly evolving automotive market of Medan City, social media marketing and brand experience have emerged as crucial factors in fostering brand loyalty among MPV car users by enhancing customer engagement. The purpose of this study is to find out and analyze the influence of social media marketing and brand experience on brand loyalty through customer engagement in MPV product users in Medan City. The sample was drawn using purposive sampling with sample criteria, namely consumers who use cars with the Toyota brand and have used them for more than 3 (three) years. The sample calculation used the slovin formula with a total of 397 respondents. The research data used primary data and secondary data. The data analysis carried out is path analysis. The results of sub-1 analysis show that social media marketing and brand experience have a positive and significant effect on customer engagement. The results of sub-2 analysis show that social media marketing and brand experience have a positive and significant effect on brand loyalty through customer engagement.